Relapse after treatment withdrawal of antiepileptic drugs for Juvenile Absence Epilepsy and Juvenile Myoclonic Epilepsy. (July 2018) - Healy, Liam; Moran, Maria; Singhal, Sumeet; O'Donoghue, Michael F.; Alzoubidi, Rania; Whitehouse, William P.
Highlights: A high number of patients with JME and JAE in remission withdrew from AEDs. All patients with JAE and 80% of patients with JME relapsed after AED withdrawal. 25% of patients with JAE continuing on AEDs relapsed. 36% of patients with JME continuing on AEDs relapsed. Abstract: Purpose: Conventional teaching is that juvenile myoclonic epilepsy (JME) and juvenile absence epilepsy (JAE) require lifelong antiepileptic drug (AED) treatment. We therefore wanted to determine how many patients attending our epilepsy service with JAE or JME went into 2 year remission, and then relapsed, both off and on AEDs. Method: This was a retrospective case-notes review. Patients with JAE and JME were systematically ascertained from clinic lists and databases at one teaching hospital. Data was extracted systematically. Simple descriptive statistics were used. Results: JAE: 14/36 (39%) were seizure free on AEDs for at least 2 years. Of the 6 (43%) attempting AED withdrawal, all (100%) relapsed, compared with only 25% of those who did not withdraw AEDs. Only 2/5 who relapsed and restarted AEDs regained remission. JME: 32/145 (22%) were seizure free on AEDs for at least 2 years. Of the 10 (31%) attempting AED withdrawal, 8 (80%) relapsed, compared with only 36% of those who did not withdraw AEDs. Only 2/8 who relapsed and restarted AEDs regained remission. Conclusion: Remission rates for JAE and JME was lower than expected. Higher proportions of seizure free patients underwent physician-supervised withdrawal than anticipated. Relapse rates off AEDs were similar for JAE and JME, and at least twice as high as for those remaining on AEDs, and a further remission was not invariable on restarting AEDs. Our experience, comparing relapse in those withdrawing to those staying on AEDs will help in discussions with patients keen to try AED withdrawal.